2021
DOI: 10.4254/wjh.v13.i8.926
|View full text |Cite
|
Sign up to set email alerts
|

Clostridioides difficile infection in liver cirrhosis patients: A population-based study in United States

Abstract: BACKGROUND Clostridioides (formerly Clostridium ) difficile infection (CDI) is an increasingly frequent cause of morbidity and mortality in hospitalized patients. Multiple risk factors are documented in the literature that includes, but are not limited to, antibiotics use, advanced age, and gastric acid suppression. Several epidemiological studies have reported an increased incidence of CDI in advanced liver disease patients. Som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…Firstly, studies have shown females to be more prone to CDI [ 50 ]. This was confirmed in a couple of studies on cirrhosis patients [ 22 , 30 , 32 , 38 , 47 ]. Experimental and human studies have demonstrated differences in the gut microbiome concerning gender, and such effects are mediated by sex hormone levels [ 51 , 52 ].…”
Section: Risk Factorsmentioning
confidence: 53%
See 2 more Smart Citations
“…Firstly, studies have shown females to be more prone to CDI [ 50 ]. This was confirmed in a couple of studies on cirrhosis patients [ 22 , 30 , 32 , 38 , 47 ]. Experimental and human studies have demonstrated differences in the gut microbiome concerning gender, and such effects are mediated by sex hormone levels [ 51 , 52 ].…”
Section: Risk Factorsmentioning
confidence: 53%
“…Several studies have reported the prevalence of CDI in patients with cirrhosis using large nationwide databases. In a study conducted in an extensive commercial database in the US, the prevalence of CDI in cirrhosis was 134.93 per 100,000 of 133,400 patients diagnosed with cirrhosis between 2018–2021 [ 30 ]. Nationwide Readmissions Database (NRD) in the US revealed that the prevalence of CDI in patients with cirrhosis was 2.8% from 2011 to 2014, with higher inpatient mortality compared with cellulitis and urinary tract infections (UTI) (17.6% vs. 7.6%, 11.8%), respectively, and the presence of sepsis and organ failure was also most common in CDI [ 31 ].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, CLD is also associated with changes in the gut microbiome and bile acid synthesis, both of which have been shown to increase CDI [ 23 ]. Keeping the above mechanisms in mind, multiple studies have shown that CDI and COVID-19 are individually associated with higher morbidity and mortality in patients with CLD [ 21 , 24 , 25 , 26 ]. Therefore, it was no surprise that that our study collectively found CDI and COVID-19 to have a positive association with CLD.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-six articles included a risk estimate for sex (Fig. 2); a significantly higher risk of CDI in women compared with men was reported in 12 studies [28,43,[47][48][49][50][51][52][53][54][55]. This ranged from an aOR of 1.02 (95% CI 1.00-1.04; p value not presented) in a mixed study population in a large database study [34] to an aOR of 6.3 (95% CI 1.7-24.0; p \ 0.01) in patients with urinary tract infections (UTIs) [50].…”
Section: Risk Factors For CDImentioning
confidence: 99%